The Role of Corporate-Customer Relationship in Business Success - Chand, Bhoj Bahadur (KVM Research Journal, 2025)
Corporate-customer relationship is a critical factor that influences the success and sustainability of businesses in today’s competitive market. Establishing strong and positive relationships with customers not only enhances loyalty and satisfaction but also drives repeat business, brand advocacy, and long-term profitability. This study examines the strategies employed by corporations to build effective customer relationships, including personalized services, proactive communication, feedback mechanisms, and trust-building initiatives. The research also highlights the challenges businesses face in maintaining consistent engagement with customers, such as evolving consumer expectations, technological changes, and market competition. By analyzing theoretical frameworks and empirical evidence, the study demonstrates that businesses with strong customer relationships experience higher retention rates, better financial performance, and sustainable growth. The findings underline the importance of adopting customer-centric approaches, integrating technology in relationship management, and fostering continuous improvement to strengthen corporate-customer bonds and achieve business success.